Entwickeln sich wirtschaftswissenschaftliche Forschung und Politikberatung auseinander? Warum engagieren sich nicht mehr ökonomische Spitzenforscher in der Politikberatung? - Justus Haucap; Michael Mödl (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
Die mangelnde Relevanz wirtschaftswissenschaftlicher Forschung wird nicht nur in Deutschland und nicht erst seit der Finanz- und Wirtschaftskrise (und dem in Deutschland resultierenden Ökonomenstreit) und nicht nur in Politik und Medien beklagt. So hat z. B. Marc Blaug schon 1997 sein Unbehagen über die Ausrichtung der modernen Ökonomie geäußert: '(...) modern economics is sick; economics has increasingly become an intellectual game played for its own sake and not for its practical consequences' (Blaug 1997, S. 3). Ein Jahrzehnt später hat Gregory Mankiw (2007) diese Kritik, wenn auch mit etwas anderem Zungenschlag, in seiner Auseinandersetzung mit der sog. Freakonomie in seinem Blog wiederholt: '[M]ore young economists today are doing Levitt-style economics and fewer are studying the classic questions of economic policy. That is disconcerting, to a degree. It could be especially problematic twenty years from now, when President Chelsea Clinton looks for an economist to appoint to head the Federal Reserve, and the only thing she can find in the American Economic Association are experts on game shows and sumo wrestling'. (...)
Keywords: 330